Restricted expression of Slap-1 in the rodent cerebral cortex. - Alifragis, P; Molnár, Z; Parnavelas, J (2003)
The deep layers of the mammalian cerebral cortex contain pyramidal neurons that project predominantly to subcortical targets. To understand the mechanisms that determine the identity of deeper layer neurons, a PCR based subtractive hybridisation was performed to isolate genes that are specifically expressed during the specification of these neurons. One of the genes we isolated was the rat homologue of the mouse Slap-1. SLAP-1 is an adaptor protein containing SH2-SH3 domains and it participates in the signalling of Receptor Tyrosine Kinases. In situ hybridisation studies have shown that Slap-1 is not substantially expressed before E17. At later stages, it is specifically and selectively expressed by deeper layer neurons and by neurons of layers II/III in the developing cortex. The specific timing and location of its expression, suggests that this gene may play a role in the differentiation of these neurons.